HUBUNGAN GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA ORGANISASI DI DINAS PEMADAM KEBAKARAN KOTA BEKASI - Imam Wahyudi; Ari Subowo; Dyah Hariani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
In this study, researchers tried to discuss the Relationship between Leadership Style and Work Environment on Organizational Performance at the Bekasi City Fire Department. What is none other than the purpose of the research results is oriented to find out the relationship of leadership style to organizational performance, the relationship of work environment to organizational performance, and the relationship of leadership style and work environment to organizational performance in the Bekasi City Fire Department. In the preparation of research using a type of quantitative approach with associative analysis to determine the relationship between variables. The technique used for sampling used the slovin formula with an error rate of 5% and the samples obtained based on the formula amounted to 75 respondents. In the hypothesis section, tests were carried out using cross-tabulation analysis, Kendall's rank correlation coefficient, determination coefficient, and Kendall's concordance coefficient. According to the results of analysis and data processing, it can be determined that the relationship to organizational performance in the Bekasi City Fire Department is as follows: there is a positive (directional), significant and weak but definite relationship in leadership style (X1) with organizational performance (Y), then there is positive relationship (directional), significant and weak but sure value in the work environment (X2) with organizational performance (Y). Then also found a positive and significant relationship between Leadership Style and Work Environment together with Organizational Performance.